Transnationalization as a direction of global changes in current economic space - Zanozovska, Oksana (My University, 2014)
The transformation of the world order and its transition exacerbate the problems of national interest and identity.Globalization processesaffecting the developmentof many countriesof the world,including theUkraine, defining rolefor herparty tosuch processes.Nowquite difficultto predicteconomic future of Ukraine,butin the new environmentmarkedturn towards. Westernvaluesandlifestyletrade-market economy, as a result there isa danger ofloss of nationalcultural identity.Therefore, insuch circumstances,Ukraineneeds tofindits own waytoglobalization.
Keywords: transnationalization; global change; economy; транснаціоналізація; глобальні зміни; економіка; транснационализация; глобальные изменения; экономика; кафедра міжнародної економіки